Tax Avoidance, Large Positive Temporary Book-Tax Differences, and Earnings Persistence - Blaylock, Bradley; Shevlin, Terry; Wilson, Ryan J. (The Accounting Review, 2012)
ABSTRACT We investigate why temporary book-tax differences appear to serve as a useful signal of earnings persistence (Hanlon 2005). We first test and show that temporary book-tax differences provide incremental information over the magnitude of accruals for the persistence of earnings and accruals. We then opine that there are multiple potential sources of large positive book-tax differences. We predict and find that firms with large positive book-tax differences likely arising from upward earnings management (tax avoidance) exhibit lower (higher) earnings and accruals persistence than do other firms with large positive book-tax differences. Finally, we find significant variation in current-period earnings and accruals response coefficients and insignificant hedge returns in period t+1, consistent with investors being able to look through to the source of large positive book-tax differences (earnings management and tax avoidance), allowing them to correctly price the persistence of accruals for these subsamples. Data Availability: Data are available from public sources identified in the study.